INNOVATIVE APPROACH TO FERTILITY RESTORATION IN WOMEN OF LATE REPRODUCTIVE AGE WITH LOW OVARIAN RESERVE - Shukurov, F.I.; Akhmedzhanova, K.Z.; Ismoilova, Sh.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Fertility restoration in women of late reproductive age with low ovarian reserve is one of the pressing challenges in modern reproductive medicine. The decline in ovarian reserve, combined with age-related changes, limits the chances of natural conception, increases the risk of reproductive failures, and prompts specialists to seek effective and safe stimulation methods. The aim of the study. Evaluation of the Effectiveness of PRP Therapy in Combination with a Clomiphene-Containing Drug for Fertility Restoration in Women of Late Reproductive Age with Low Ovarian Reserve Materials and methods. The study included 110 women of late reproductive age with low ovarian reserve. Among them, 60 women with low ovarian reserve who received PRP therapy (Group I), and 50 women with extremely low ovarian reserve who received PRP therapy in combination with a clomiphene-containing drug (Group II). The control group consisted of 30 healthy women. All patients underwent a comprehensive clinical-laboratory, hormonal, immunological, and instrumental examination. Results. The results showed that the use of PRP therapy in combination with a clomiphene-containing drug in women of late reproductive age with low and extremely low ovarian reserve led to ovulation in 75.3% and 72.5% of women, respectively, as well as pregnancy in 73.3% and 62.5% in these groups.. Conclusion. The use of PRP therapy in combination with a clomiphene-containing drug in women of late reproductive age with low and extremely low ovarian reserve led to a 2.2-fold reduction in infertility rates, a 2.2-fold increase in fertility restoration, and a fourfold reduction in treatment costs, highlighting both the medical and economic effectiveness of this approach.